Study of recreational health routes in Stavropol using geoinformation technologies - M. V. Katrenko; N. S. Gorbaneva; L. V. Yukhtenko; Yu. I. Zhuravleva; Z. M. Zapirov (Вестник Северо-Кавказского федерального университета)
Introduction. Successful self-realization of a person in life, first of all, depends on their health. Physical activity refers to the implementation of rehabilitation measures to maintain health. In terms of solving the designated problem, the article proposes a combination of health forms and comfortable environmental conditions. The use of geoinformation system technologies in the work made it possible to study the routes of Stavropol in terms of recreational jogging.Goal. The study specifies the preferences of people engaged in physical activity in choosing jogging routes in Stavropol. Materials and methods. The study is based on literature review, conducting a sociological survey and summarizing the results. Results and discussion. The results of the study allowed the authors to conduct a comparative analysis of the running routes of Stavropol. Conclusion. Formulate the conclusion that visual examination and the use of route maps in choosing the proposed routes had a positive impact on those involved and contributed to the active inclusion of more people in recreational health activities.